2015
DOI: 10.33119/kkessip.2015.3.3.10
|View full text |Cite
|
Sign up to set email alerts
|

Zastosowanie miar maksymalnej straty na kapitale w badaniu efektywności funduszy hedgingowych

Abstract: The paper presents research on hedge funds efficiency with such measuresas Calmar ratio, Sterling ratio and Burke ratio carried out using the data fromHedge Fund Research database for 2005–2011. The aim of the study is to answerthe question whether alternative efficiency measurs are really more adequate for assessing the efficiency of hedge fund investments. So far, the answer to thisquestion is surprisingly negative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…On the domestic market, research related to the measurement of effectiveness is found in a study by Pruchnicka-Grabias [2015]. The article emphasizes that calculating various new measures of investment risk does not contribute to the improvement of the efficiency measurements.…”
Section: Review Of the Research Literature On Investment Performancementioning
confidence: 99%
“…On the domestic market, research related to the measurement of effectiveness is found in a study by Pruchnicka-Grabias [2015]. The article emphasizes that calculating various new measures of investment risk does not contribute to the improvement of the efficiency measurements.…”
Section: Review Of the Research Literature On Investment Performancementioning
confidence: 99%